PENGARUH KOMUNIKASI TERHADAP KINERJA PEGAWAI BAGIAN TATA USAHA PADA SMA NEGERI 1 MADANG SUKU I OGAN KOMERING ULU TIMUR - Putri Martin, Tamara (Jurnal Trisna Riset, 2022)
In supporting the progress and development of an organization, it is very important to carry out these efforts seriously and sustainably in various fields and all aspects of life. The availability of quality human resources and a high work ethic is the main capital for an organization to be able to compete with other organizations. At SMA Negeri 1 Madang Suku I Ogan Komering Ulu Timur, communication has not been implemented optimally, so that the performance of administrative staff has not reached the expected level. The problem faced is how does communication influence the performance of administrative staff at SMA Negeri 1 Madang Suku I Ogan Komering Ulu Timur. The aim of this research is to determine the effect of Communication on the Performance of Administrative Department Employees at SMA Negeri 1 Madang, East Ogan Komering Ulu Tribe and to be useful as reference material for further research regarding Communication and Performance of Administrative Section Employees. The hypothesis proposed is that communication has a positive effect on the performance of administrative staff at SMA Negeri 1 Madang Suku 1 Ogan Komering Ulu Timur. Data collection and processing using library studies and field studies using observation, questionnaires, interviews and documentation. From the results of the discussion and statistical calculations, it was found that the correlation between Communication in an effort to improve the Performance of Administration Department Employees at SMA Negeri 1 Madang Suku I Ogan Komering Ulu Timur obtained an r number of 0.65. After consulting with conservative standards, it is between 0.600-0.799 which is considered a strong correlation. So it can be said that there is a strong influence between Communication on the Performance of Administration Department Employees at SMA Negeri 1 Madang Suku I Ogan Komering Ulu Timur.